Physiological and Pathological Vaginal Microflora in the Bitch - Anton Antonov (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
The vagina is a place for the development of various physiological microorganisms, so cultures of the vaginal cavity almost always result in growth of bacteria. Together with the cervix, the vagina of the mammals also serves as a border for the microorganisms before reaching the uterus. Determination of the qualitative and quantitative characteristics of vaginal bacterial flora is of great significance for a better understanding of genital pathology mechanism, clinical diagnosis, management of reproductive diseases and effective prevention of urogenital infections in the bitch, which are a very common problem in the daily veterinary practice. The objective of this book chapter is to provide a better understanding of the vaginal microflora importance for developing infections, pathogenesis of infertility and reproductive disorders in the bitch.